2013
DOI: 10.3109/00365521.2013.828772
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal barrier function and tight junction expression in healthy subjects and patients with gastroesophageal reflux disease: functionality of esophageal mucosa exposed to bile salt and trypsin in vitro

Abstract: BACKGROUND AND AIMS. Gastroesophageal reflux disease (GERD) is associated with impaired epithelial barrier function. However, the influence of acid and/or bile acids on human esophageal epithelial barrier function and the tight junction (TJ) proteins has not been fully elucidated. The aim of the study is to investigate the esophageal barrier function and TJ expression in healthy subjects and patients with GERD. The functionality of esophageal mucosa exposed to bile salt deoxycholic acid (DCA) and trypsin has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 25 publications
4
50
1
7
Order By: Relevance
“…Although no change in occludin or ZO-1 expression has been reported in GERD patients, the expression of CLDN1 and CLDN2 mRNA and protein has been reported to be increased [34] and unchanged [35] in GERD, and the expression of CLDN1 and CLDN4 has been reported to be decreased in GERD [33]. The reason for these inconsistent results may be due to the fact that total CLDN protein was measured rather than a specific subpopulation of CLDNs.…”
Section: Involvement Of Tj Proteins In Diseases Gastroesophageal Reflcontrasting
confidence: 38%
See 1 more Smart Citation
“…Although no change in occludin or ZO-1 expression has been reported in GERD patients, the expression of CLDN1 and CLDN2 mRNA and protein has been reported to be increased [34] and unchanged [35] in GERD, and the expression of CLDN1 and CLDN4 has been reported to be decreased in GERD [33]. The reason for these inconsistent results may be due to the fact that total CLDN protein was measured rather than a specific subpopulation of CLDNs.…”
Section: Involvement Of Tj Proteins In Diseases Gastroesophageal Reflcontrasting
confidence: 38%
“…In an analysis of esophageal biopsy specimens using an Ussing chamber, the resistance of esophageal mucosa was lower in patients with GERD than in healthy controls, indicating a loss of barrier function in GERD [31][32][33]. Although no change in occludin or ZO-1 expression has been reported in GERD patients, the expression of CLDN1 and CLDN2 mRNA and protein has been reported to be increased [34] and unchanged [35] in GERD, and the expression of CLDN1 and CLDN4 has been reported to be decreased in GERD [33].…”
Section: Involvement Of Tj Proteins In Diseases Gastroesophageal Reflmentioning
confidence: 99%
“…Epithelial thickness, particularly basal cell layer thickness, was also confirmed in GERD [17]. Other studies have reported that tight junction proteins, such as claudin-1, are altered in patients with GERD [18]. These results indicate that impaired esophageal barrier function plays a role in causing GERD symptoms.…”
Section: Introductionsupporting
confidence: 61%
“…Recently, impaired mucosal integrity was confirmed in several studies [16, 18, 19, 25, 26, 33, 36, 37]. If endoscopy-guided measurements of mucosal integrity are applied more widely, they may be of great benefit in clinical practice.…”
Section: Future Perspectivementioning
confidence: 91%
“…19,20 The esophageal epithelium from GERD patients had lower electrical resistance and higher epithelial currents than controls. 21 During gastro-esophageal reflux, luminal acid caused injury of the esophageal epithelium by altering the apical junction complexes and caused an early increase in paracellular permeability and dilated intercellular space. 22 The acid then penetrated the intercellular spaces to initiate a cascade that results in cell necrosis, inflammation, and erosion.…”
Section: Discussionmentioning
confidence: 99%